Diabetes in Patients With Ataxia Telangiectasia: A National Cohort Study - Donath, Helena; Hess, Ursula; Kieslich, Matthias; Theis, Marius; Ohlenschläger, Ute; Schubert, Ralf; Woelke, Sandra; Zielen, Stefan (Frontiers in Pediatrics, 2020)
Background: Ataxia telangiectasia (A-T) is a rare autosomal-recessive multisystem disorder characterized by pronounced cerebellar ataxia, telangiectasia, cancer predisposition and altered body composition. In addition, evidence is rising for endocrine dysfunction. Objectives: To determine the evolution of diabetes and its prevalence in a larger A-T cohort. Methods: A retrospective analysis of the patient charts of 39 subjects from the Frankfurt A-T cohort was performed between August 2002 and 2018 concerning HbA1c and oral glucose tolerance (OGTT). The median follow-up period was 4 years (1–16 years). In addition, in 31 A-T patients aged 1 to 38 years HbA1c and fasting glucose were studied prospectively from 2018 to 2019. Results: In the retrospective analysis, we could demonstrate a longitudinal increase of HbA1c. The prospective analysis showed a significant increase of HbA1c and fasting glucose with age (r = 0.79, p ≤ 0.0001). OGTT has a good sensitivity for insulin resistance screening, whereas HbA1c can be used to evaluate individual courses and therapy response. Seven out of 39 (17.9%) patients suffered from diabetes. Metformin did not always lead to sufficient diabetes control; one patient was treated successfully with repaglinide. Conclusion: Diabetes is a common finding in older A-T patients and often starts in puberty. Our data clearly demonstrate the need for an annual diabetes screening in patients > 12 years.